1991
DOI: 10.1007/bf00315225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ursodeoxycholic acid (UDCA) on serum liver damage indices in patients with chronic active hepatitis

Abstract: The effects of ursodeoxycholic acid (UDCA, 450 mg daily) in patients with histologically proven chronic active hepatitis (CAH) have been evaluated in a randomized, double-blind, placebo-controlled study. Twenty-six patients with serum alanine aminotransferase (ALT) values at least twice the normal upper limit in two of three pre-treatment tests received UDCA or a placebo for twelve weeks. In all UDCA-treated patients, serum aspartate amino-transferase (AST), ALT, gamma-glutamyl transpeptidase (GGT) and alkalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…However, the efficacy of UDCA for attenuating hepatobiliary damages seemed beyond doubt, and several studies have demonstrated the efficacy of UDCA in this respect. 24,25 There was no statistically significant difference in the ratio of reduction in ALP levels between the group that received prior treatment with UDCA and that which did not ( Table 2). The main mechanism by which UDCA lowers serum biliary enzyme levels is thought to be the replacement of toxic bile salts with nontoxic hydrophobic ones, which differs from the mechanism of bezafibrate, as mentioned earlier.…”
Section: Discussionmentioning
confidence: 58%
“…However, the efficacy of UDCA for attenuating hepatobiliary damages seemed beyond doubt, and several studies have demonstrated the efficacy of UDCA in this respect. 24,25 There was no statistically significant difference in the ratio of reduction in ALP levels between the group that received prior treatment with UDCA and that which did not ( Table 2). The main mechanism by which UDCA lowers serum biliary enzyme levels is thought to be the replacement of toxic bile salts with nontoxic hydrophobic ones, which differs from the mechanism of bezafibrate, as mentioned earlier.…”
Section: Discussionmentioning
confidence: 58%
“…[7][8][9] In primary biliary cirrhosis, an improved survival rate and liver morphology have been shown. 8,10 In CF, UDCA has been shown to improve LFT and to ameliorate the hepatic wash-out of isotope at hepatobiliary scintigraphy.…”
mentioning
confidence: 99%
“…It reduces the effect of hydrophobic bile acids on the hepatocytes through its choleritic and anti‐apoptotic effects (12). In addition, it decreases hepatitis C virus‐related hepatic injury by modifying the expression of HLA‐Class I and reinforces the natural antiviral mechanisms such as natural killer cells, 2″, 5″ oligo adenylate synthetase activity thus degrading viral mRNA (13, 14). UDCA was shown to achieve normalization of serum transaminases twice as much as amantadine hydrochloride or silymarin (15).…”
Section: Discussionmentioning
confidence: 80%